Expression of the phagocytic receptors αMβ2 and αXβ2 is controlled by RIAM, VASP and Vinculin in neutrophil-differentiated HL-60 cells - Torres-Gomez, Alvaro; Fiyouzi, Tara; Guerra-Espinosa, Claudia; Cardeñes, Beatriz; Clares, Irene; Toribio, Víctor; Reche, Pedro A.; Cabañas, Carlos; Lafuente, Esther M. (Frontiers in Immunology, 2022)
Activation of the integrin phagocytic receptors CR3 (αMβ2, CD11b/CD18) and CR4 (αXβ2, CD11c/CD18) requires Rap1 activation and RIAM function. RIAM controls integrin activation by recruiting Talin to β2 subunits, enabling the Talin-Vinculin interaction, which in term bridges integrins to the actin-cytoskeleton. RIAM also recruits VASP to phagocytic cups and facilitates VASP phosphorylation and function promoting particle internalization. Using a CRISPR-Cas9 knockout approach, we have analyzed the requirement for RIAM, VASP and Vinculin expression in neutrophilic-HL-60 cells. All knockout cells displayed abolished phagocytosis that was accompanied by a significant and specific reduction in ITGAM (αM), ITGAX (αX) and ITGB2 (β2) mRNA, as revealed by RT-qPCR. RIAM, VASP and Vinculin KOs presented reduced cellular F-actin content that correlated with αM expression, as treatment with the actin filament polymerizing and stabilizing drug jasplakinolide, partially restored αM expression. In general, the expression of αX was less responsive to jasplakinolide treatment than αM, indicating that regulatory mechanisms independent of F-actin content may be involved. The Serum Response Factor (SRF) was investigated as the potential transcription factor controlling αMβ2 expression, since its coactivator MRTF-A requires actin polymerization to induce transcription. Immunofluorescent MRTF-A localization in parental cells was primarily nuclear, while in knockouts it exhibited a diffuse cytoplasmic pattern. Localization of FHL-2 (SRF corepressor) was mainly sub-membranous in parental HL-60 cells, but in knockouts the localization was disperse in the cytoplasm and the nucleus, suggesting RIAM, VASP and Vinculin are required to maintain FHL-2 close to cytoplasmic membranes, reducing its nuclear localization and inhibiting its corepressor activity. Finally, reexpression of VASP in the VASP knockout resulted in a complete reversion of the phenotype, as knock-ins restored αM expression. Taken together, our results suggest that RIAM, VASP and Vinculin, are necessary for the correct expression of αMβ2 and αXβ2 during neutrophilic differentiation in the human promyelocytic HL-60 cell line, and strongly point to an involvement of these proteins in the acquisition of a phagocytic phenotype.